Heavy metals in water associated with oil and soil were treated using chemical and electrophoretic precipitation methods. - AB. Matter, Hamdy; emgharbi, Mohamed (Scientific Journal of University of Benghazi, 2025)
Chemicals such as potassium hydroxide (KOH), potassium ferrocyanide (K₄[Fe(CN)₆]), and oxalic acid (H₂C₂O₄) have been used as agents capable of rapidly and efficiently forming precipitates with heavy metal ions under natural environmental conditions. The active components in these chemicals act as chelating agents, enabling them to form stable precipitates or complexes with heavy metals present in water associated with oil and in the surrounding soil. This study compares the efficiency and characteristics of chemical precipitation products with those formed via cathodic deposition during electrochemical treatment. The ability of both methods to precipitate various heavy metals (HMs)—including Cr, Fe, Ni, Mg, Cu, Zn, Ag, Cd, Mn, and Pb—was investigated. Each method demonstrated varying effectiveness in removing specific metals, and it was measured deposition efficiency, standard deviation S and a coefficient of variation (CV). Chemical and electrical methods have treated oil-related water and soil contaminated with common heavy metals, which could be removed and treated chemically and electrically. The results revealed very high concentrations of these harmful heavy metals, which have contaminated oil-related water, the soil, the groundwater beneath it, and the plants it irrigates. This poses risks to human and animal health and may even cause diseases and cancer.